2022
DOI: 10.1161/strokeaha.122.035816
|View full text |Cite
|
Sign up to set email alerts
|

Health Equity and Actionable Disparities in Stroke: 2021 Update

Abstract: There are stark inequities in stroke incidence, prevalence, acute care, rehabilitation, risk factor control, and outcomes. To address these inequities, it is critical to engage communities in identifying priorities and designing, implementing, and disseminating interventions. This issue of Stroke features health equity themed lectures delivered during the International Stroke Conference and Health Equity and Actionable Disparities in Stroke: Understanding and Problem-Solving meetings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Therefore, disadvantaged people in Iran are struggling more with adversities related to disability and need much more attention from policymakers. It is believed that people with disabilities may use less health services ( 34 ).This confirmed the finding of a study in Iran where it showed that the use of rehabilitation services has been concentrated among privileged Iranians ( 35 ). This requires the attention of the healthcare authorities for an equitable distribution of these services .…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, disadvantaged people in Iran are struggling more with adversities related to disability and need much more attention from policymakers. It is believed that people with disabilities may use less health services ( 34 ).This confirmed the finding of a study in Iran where it showed that the use of rehabilitation services has been concentrated among privileged Iranians ( 35 ). This requires the attention of the healthcare authorities for an equitable distribution of these services .…”
Section: Discussionsupporting
confidence: 76%
“… 35 , 36 Progress in this realm demonstrates the positive cumulative effects of efforts that have been made to address inequities within stroke and health care more broadly. 37 While some of these trends are positive, the goal of true health equity has not been achieved, particularly in reference to individual‐ and system‐level factors that contribute to racial and ethnic disparities within health care. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Accelerated by the COVID-19 pandemic, health care disparities and inequities based on race and ethnicity have garnered greater attention. Our understanding of health equity in neuromuscular disorders is far more limited than in other areas of neurology . Improved recognition, appreciation, and rectification of neuromuscular disparities has direct implications in improving the quality of care for vulnerable populations.…”
mentioning
confidence: 99%